Prevention of Central Line-Associated Bloodstream Infections Through Educational Interventions in Adult Intensive Care Units: A Systematic Review - Foka, Maria; Nicolaou, Eleni; Kyprianou, Theodoros; Palazis, Lakis; Kyranou, Maria; Papathanassoglou, Elizabeth; Lambrinou, Ekaterini (My University, 2021)
Central line-associated bloodstream infections (CLABSIs) represent a severe systemic threat to patients admitted in ICUs and contribute to increased mortality, prolonged length of stay in ICUs, and increased costs. The majority of CLABSIs are preventable. The current systematic review aimed to investigate the effectiveness of educational methods on CLABSI rates in adult ICUs. A systematic literature search was conducted using the electronic databases of Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL) Plus, and Cochrane Database of Systematic Reviews for studies published from the beginning of 1995 to March 2020. The terms used for the search were as follows: central venous catheters, infection, central line-associated bloodstream infections, intensive care unit, and education intervention in all possible combinations and using the word ‘and’ between them. Data were extracted independently and crosschecked by two authors using a standard data collection form. The quality of the studies included in the review was assessed using the Methodological Index for Non-randomized Studies (MINORS). The current systematic review included 27 interventional studies of central line insertion or maintenance or both in adult ICU settings with documentation of the CLABSI incidence expressed per 1,000 catheter days. A large deviation between the length of time and type of educational interventions was found. Statistical significance was found in all studies (except one) in terms of CLABSI reduction despite the large variation of the length or the type of the educational intervention. Continuing education on infection prevention may be necessary to maintain the post-intervention results and improve clinical outcomes.
Keywords: Central venous catheters; Infection; Central line associated bloodstream infections; Intensive care unit; Education; Intervention